Case of urinary mycobacterium fortuitum in a patient with urinary tract tuberculosis posttreatment - Maehana, Takeshi (Hinyokika kiyo. Acta urologica Japonica, 2008)
A 70-year-old male who complained of urinary frequency and a feeling of incomplete emptying was admitted to our hospital. Imaging findings showed dilation of the left renal pelvis and ureter. He was diagnosed as having urinary tuberculosis because a positive urinary Mycobacterium tuberculosis result was obtained by polymerase chain reaction (PCR). He was treated with a combination of the antituberculosis agents isoniazid, rifampicin, pyrazinamide and ethambutol for six months. The symptoms and pyuria disappeared and M. tuberculosis was negative by PCR; however, Mycobacterium fortuitum was isolated by culture. Due to asymptomatic urinary tract infection by the multidrug resistant M. fortuitum, he was followed up with observation. Currently, he remains unchanged with regard to symptoms and imaging examination. M. fortuitum is a nontubercular mycobacterium, and clinical relevance between urinary tract infection and M. fortuitum has rarely emerged. However, we should be aware that nontubercular mycobacteria such as M. fortuitum can infect the urinary tract, especially in immunocompromised patients